Prevalence of River Epilepsy in the Orientale Province in the Democratic Republic of the Congo. - Robert Colebunders; Floribert Tepage; Ente Rood; Michel Mandro; Emmanuel Nji Abatih; Gisele Musinya; Germain Mambandu; José Kabeya; Michel Komba; Bethany Levick; John L Mokili; Anne Laudisoit (Public Library of Science (PLoS), 2016)
BACKGROUND:An increased prevalence of epilepsy has been reported in many onchocerciasis endemic areas. OBJECTIVE:To determine the prevalence and distribution of epilepsy in an onchocerciasis endemic region in the Democratic Republic of the Congo (DRC). DESIGN/METHODS:An epilepsy prevalence study was carried out in 2014, in two localities of the Bas-Uélé district, an onchocerciasis endemic region in the Orientale Province of the DRC. Risk factors for epilepsy were identified using a random effects logistic regression model and the distribution of epilepsy cases was investigated using the Moran's I statistic of spatial auto-correlation. RESULTS:Among the 12,776 individuals of Dingila, 373 (2.9%) individuals with epilepsy were identified. In a house-to-house survey in Titule, 68 (2.3%) of the 2,908 people who participated in the survey were found to present episodes of epilepsy. Epilepsy showed a marked spatial pattern with clustering of cases occurring within and between adjacent households. Individual risk of epilepsy was found to be associated with living close to the nearest fast flowing river where blackflies (Diptera: Simuliidae)-the vector of Onchocerca volvulus-oviposit and breed. CONCLUSIONS:The prevalence of epilepsy in villages in the Bas-Uélé district in the DRC was higher than in non-onchocerciasis endemic regions in Africa. Living close to a blackflies infested river was found to be a risk factor for epilepsy.